Disordered Gut Microbiota Correlates With Altered Fecal Bile Acid Metabolism and Post-cholecystectomy Diarrhea - Xu, Yayun; Jing, Hui; Wang, Jianfa; Zhang, Shilong; Chang, Qimeng; Li, Zhanming; Wu, Xubo; Zhang, Ziping (Frontiers in Microbiology, 2022)
Post-cholecystectomy diarrhea (PCD) is a common complication of gallbladder removal and gut microbiota changes have been determined in PCD patients. Bile acid diarrhea (BAD) is supposed to be the main pathogenic factor for PCD due to the disrupted fecal bile acid metabolism in diarrheal patients. However, the profiling of bile acid metabolites alteration in PCD is unclear and whether changed gut microbiota and fecal bile acid metabolism are correlated is also underdetermined. The fecal bile acid metabolites from fecal samples were profiled by targeted UPLC/MS (ultra-high-performance liquid chromatography coupled with a triple-quadrupole mass spectrometer) and the composition of fecal bile acid metabolites in PCD patients were demonstrated to be distinct from those in NonPCD and HC groups. In addition, the quantification of bile acids excretion in feces of diarrheal patients was significantly elevated. Furthermore, 16S rRNA sequencing results revealed that PCD patients contained the lowest operational taxonomic units and significant reduction in microbial richness and evenness. Bacterial composition was remarkably shifted in PCD patients, which mainly lied in dominated phyla Firmicutes and Bacteroidota. Besides, the co-abundance network among genus bacteria declined in PCD. In genus, Prevotella, Enterococcus and Erysipelotrichaceae_UCG-003 were enriched, but Alistipes, Bacteroides, Ruminococcus and Phascolarctobacterium were reduced. Moreover, these diseased-linked genera were closely associated with several diarrheal phenotypes. Notably, changed bile acid metabolites exhibited strong correlations with gut microbiota as well. Conclusively, this study reveals associations between PCD-linked microbes and bile acid metabolites, which may synergistically correlate to postoperative diarrhea.